Urban farming untuk ketahanan pangan: Studi kasus Kelurahan Pedalangan, Semarang - Riyan Firmansyah; Roha Aria Wardani; Nur Alawiyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2026)
Urban problems are becoming increasingly complex, primarily due to rapid population growth, leading to the conversion of agricultural land into residential, industrial, and office areas. Dependence on food supplies from outside the city makes food prices unstable and vulnerable to disruptions. This research aims to address food security issues in urban areas with limited vacant land. It employs the Community-Based Research (CBR) method, emphasizing active community participation in all stages, from planning to implementation. This approach aligns with delivering relevant, sustainable solutions for the community. Researchers conducted direct field observations of urban farming processes and interviewed stakeholders. The results were used to draw conclusions and answer research questions. The urban farming program in Pedalangan Village has shown that with the right approach, active community participation, and government support, it can be a sustainable solution to meet local food needs, preserve the environment, and improve quality of life. However, it faces challenges such as limited land, restricted plant varieties and quantities, and time constraints due to residents' busy lives.